2019
DOI: 10.1038/s41588-019-0481-0
|View full text |Cite|
|
Sign up to set email alerts
|

A global overview of pleiotropy and genetic architecture in complex traits

Abstract: ince the first genome-wide association study on macular degeneration in 2005 (ref. 1), over 3,000 GWASs have been published, for over 1,000 traits, reporting on tens of thousands of genetic risk variants 2. These results have increased our understanding of the genetic architecture of traits. Occasionally, GWAS results have led to further insight into disease mechanisms 3,4 , such as autophagy for Crohn's disease 5 , immunodeficiency for rheumatoid arthritis 6 and transcriptome regulation through FOXA2 in the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
734
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 948 publications
(828 citation statements)
references
References 46 publications
16
734
2
3
Order By: Relevance
“…The pattern of ASD-and ADHD-specific associations with EA, in combination with discordant polygenic cross-disorder links, was (i) reciprocally detectable using both ASD and ADHD-related variant sets, (ii) replicated at P thr <0.05 using ASD(PGC) summary statistics, (iii) independent of risk allele alignment for ASD and ADHD and (iv) consistent with the previously reported genetic overlap between EA, ASD and ADHD 21,28 . This suggests that cross-disorder associations are driven by a substantial proportion of subthreshold variants that are associated with both ASD and ADHD, reflecting pleiotropic effects, presumed for many trait-associated variants in the genome 33 . Moreover, joint modelling of these pleiotropic alleles, exploiting single instead of aggregated SNP estimates, could substantially increase evidence for both disorder-specific and cross-disorder associations.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of ASD-and ADHD-specific associations with EA, in combination with discordant polygenic cross-disorder links, was (i) reciprocally detectable using both ASD and ADHD-related variant sets, (ii) replicated at P thr <0.05 using ASD(PGC) summary statistics, (iii) independent of risk allele alignment for ASD and ADHD and (iv) consistent with the previously reported genetic overlap between EA, ASD and ADHD 21,28 . This suggests that cross-disorder associations are driven by a substantial proportion of subthreshold variants that are associated with both ASD and ADHD, reflecting pleiotropic effects, presumed for many trait-associated variants in the genome 33 . Moreover, joint modelling of these pleiotropic alleles, exploiting single instead of aggregated SNP estimates, could substantially increase evidence for both disorder-specific and cross-disorder associations.…”
Section: Discussionmentioning
confidence: 99%
“…nl/), an online database of publicly available summary results statistics from 4,155 GWAS from 295 unique studies across 2960 unique traits and 27 domains. (19) Significance for pleiotropic associations used a traditional genome-wide significance threshold for SNP-trait PheWAS (p < 5 × 10 −8 ). (17)…”
Section: Multi-marker Analysis Of Genomic Annotation (Magma) In Uk Bimentioning
confidence: 99%
“…SMAD9 HIGH BONE MASS 99 n Phenomewide association study PheWAS involving nearly 3000 traits (19) identified no clear evidence for pleiotropy for the c.65T>C, p.Leu22Pro SMAD9 variant (rs111748421) (Supplemental Fig. S6 and Supplemental Table S4 in File S1).…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
“…6F), which has not been previously shown. HNF4A is an essential TF during liver organogenesis and development [38,39] and harbors a missense mutation (rs1800961) strongly associated with liver relevant traits including high-density lipoprotein levels and total cholesterol [45,46,47] (Additional file 1: Figure S16).…”
Section: Transcription Factors Enriched In U-eqtls and Ts-eqtlsmentioning
confidence: 99%